Inhibitory Mechanisms of CME-1, a Novel Polysaccharide from the Mycelia of Cordyceps sinensis, in Platelet Activation - Chang, Yi; Hsu, Wen-Hsien; Lu, Wan-Jung; Jayakumar, Thanasekaran; Liao, Jiun-Cheng; Lin, Mei-Jiun; Wang, Shwu-Huey; Geraldine, Pitchairaj; Lin, Kuan-Hung; Sheu, Joen-Rong (Current Pharmaceutical Biotechnology, 2015)
Objective: CME-1 is a polysaccharide purified from the mycelia of medicinal mushroom Cordyceps sinensis, its molecular weight was determined to be 27.6 kDa by using nuclear magnetic resonance and gas chromatography-mass spectrometry. The initiation of arterial thromboses is relevant to various cardiovascular diseases (CVDs) and is believed to involve platelet activation. Our recent study exhibited that CME-1 has potent antiplatelet activity via the activation of adenylate cyclase/cyclic AMP ex vivo and in vivo. Methods: The aggregometry, and immunoblotting were used in this study. Results: In this study, the mechanisms of CME-1 in platelet activation is further investigated and found that CME-1 inhibited platelet aggregation as well as the ATP-release reaction, relative intracellular [Ca+2] mobilization, and the phosphorylation of phospholipase C (PLC)γ2 and protein kinase C (PKC) stimulated by collagen. CME-1 has no effects on inhibiting either convulxin, an agonist of glycoprotein VI, or aggretin, an agonist of integrin α2β1 stimulated platelet aggregation. Moreover, this compound markedly diminished thrombin and arachidonic acid (AA) induced phosphorylation of p38 mitogen-activated protein kinase (MAPK), extracellular signal-regulated kinase 2, c-Jun N-terminal kinase 1, and Akt. Treatment with SQ22536, an inhibitor of adenylate cyclase, markedly diminished the CME-1-mediated increasing of cyclic AMP level and reversed prostaglandin E1- or CME-1-mediated inhibition of platelet aggregation and p38 MAPK and Akt phosphorylation stimulated by thrombin or AA. Furthermore, phosphodiesterase activity of human platelets was not altered by CME-1. Conclusion: The crucial finding of this study is that the antiplatelet activity of CME-1 may initially inhibit the PLCγ2-PKC-p47 cascade, and inhibit PI3-kinase/Akt and MAPK phosphorylation through adenylate cyclase/ cyclic AMP activation, then inhibit intracellular [Ca+2] mobilization, and, ultimately, inhibit platelet activation. The novel role of CME-1 in antiplatelet activity indicates that this compound exhibits high therapeutic potential for treating or preventing CVDs.
Keywords: CME-1